Assessment of moringa oleifera cake residues (MOCR) as eco-friendly bio-coagulant - Zaid, Aziz Qannaf; Suriati, Ghazali; Noor Sabrina, Ahmad Mutamim; Abayomi, Olalere Olusegun; Nour, A. H. (Universiti Malaysia Pahang, 2019)
In recent times, the consumption of water for domestic and industrial use has been on an increasing trend with a rise in demand. Therefore, a need for a plant-based altervative of water treatment process at a lower cost using an environmentally friendly approach. Moringa oleifera is an example of the plant-based materials usually grown in developing countries with a natural coagulating property. In this study the Jar test was conducted to evaluate the performance of Moringa oleifera cake residue (MOCR) as biocoagulant for the treatment of water for safe drinking. The result obtained showed the lowest turbidity, pH, TDS, and water conductivity value as 4.7 NTU (0.75 mg/L), 5.2 (2.5 mg/L), 40 ppm (1.0 mg/L), and 50 µs / cm (0.50 mg/L), respectively. Hence, MOCR therefore is a potential source for plant-based coagulating agent for water treatment for domestic drinking water.